2021
DOI: 10.3390/su13073955
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Potentially Pathogenic and Antibiotic Resistant Gram-Negative Bacteria Isolated from the Danube Delta Ecosystem

Abstract: The spread of a growing number of antibiotic-resistant bacteria (ARB) outside the clinical setting into the environment has been observed. The surface water plays an important role in ARB dissemination by being both habitats and transport systems for microorganisms. The ecological and touristic importance of the Danube Delta make it a European priority for close monitoring of its freshwater system. The main goal of this paper was to analyze how the St. Gheorghe branch of the Danube Delta microbiological contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This basin represents an optimal pool for resistant pathogens and anthropogenic pollutants dissemination and accumulation throughout large and distant areas, being assigned as a reservoir of AR. Previously, it has been demonstrated that Bucharest was at the top of the most polluted sampling locations from twelve WWTPs in nine countries (Romania, Serbia, Hungary, Slovenia, Croatia, Slovakia, Czechia, Austria, and Germany) in the Danube River Basin collected and analyzed for ARGs and MGE presence [395].…”
Section: Antibiotic Resistance In Other Aquatic Ecosystemsmentioning
confidence: 99%
“…This basin represents an optimal pool for resistant pathogens and anthropogenic pollutants dissemination and accumulation throughout large and distant areas, being assigned as a reservoir of AR. Previously, it has been demonstrated that Bucharest was at the top of the most polluted sampling locations from twelve WWTPs in nine countries (Romania, Serbia, Hungary, Slovenia, Croatia, Slovakia, Czechia, Austria, and Germany) in the Danube River Basin collected and analyzed for ARGs and MGE presence [395].…”
Section: Antibiotic Resistance In Other Aquatic Ecosystemsmentioning
confidence: 99%
“…Extensive studies have been carried out to match bacterial community structure and function with different aquatic systems types. There are systems that change their physical and ecological proprieties depending on the spatio-temporal and environmental conditions [1]. Over the time, the aquatic systems have been under the pressure of natural changes and, recently, they have been more and more under anthropic pollution pressure due to a rapid development of economy and population growth [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most bacteria are very resistant and adaptive microorganisms to environmental changes mainly due to their defense mechanism based on the efflux pumps which eliminate the toxic compounds from inside cells. Bacteria could have different defense response based on the presence of harmful compounds in the environment [38,39]. Various bacterial strains (Pseudomonas aeruginosa, Staphylococcus warneri and Pseudomonas aurantica) proved to be very effective in Reldan EC40 pesticide (Nita-Lazar et al [40]) and pharmaceutical compounds metabolisation (Nita-Lazar et al [41]).…”
Section: Introductionmentioning
confidence: 99%